Pengaruh Harga, Lokasi, Promosi Penjualan dan Kualitas Pelayanan Terhadap Keputusan Pembelian Konsumen Pada Swalayan Eramart Citown's - Ikhsan, Anasrul; Zaini, Muhammad (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to analyze the influence between Price, Location, Sales Promotion, and Service Quality on Purchasing Decisions.Purchasing Decisions. The research sampling technique used Purposive Sampling technique. Data collection was carried out by distributing questionnaires physically and physical and online via Google Form to Eramart Citown's supermarket customers who have made at least two purchases. who have made a minimum purchase of two times, with a sample size of 100 respondents. The data analysis technique uses IBM SPSS 26 software. With the validity test method, reliability test, classical assumption test, multiple linear regression test and hypothesis testing. The results This study shows (1) Price has a positive and insignificant effect on purchasing decisions. on Purchasing Decisions. (2) Location has a positive and significant effect on Purchasing Decisions. (3) Sales Promotion has a positive and significant effect on Purchasing Decisions. (4) Service Quality has a positive and significant effect on Purchasing Decisions. (5) Price, Location, Sales Promotion Sales, and Service Quality on Purchasing Decisions.